Anteroposterior view of the knee does not reliably replace the lateral view during evaluation of femoral torsion: a case series. Issue 6 (November 2020) - Hadeed, Michael M.; Fashandi, Ahmad H.; Novicoff, Wendy; Yarboro, Seth R.
Abstract : Background: Restoration of anatomic torsion is a critical step in operative fixation of femoral shaft fractures. Several accepted methods use the morphology of the femur to determine torsion. The anteroposterior view of the knee has been used to simplify the procedure, yet this method has not been validated. The purpose of this study was to evaluate native distal femoral and patellar anatomy to compare the reliability of using the anteroposterior view, which includes landmarks outside of the femur, to using the lateral view, which uses only femoral morphology, for establishing appropriate torsion in femoral shaft fractures. Methods: Fifteen patients without a history of lower extremity fractures participated. Each participant had anteroposterior and lateral images taken of their femurs. Data were compared between repetitions of a single limb, two legs of a single patients, and between patients. Intrarater and interrater reliability were measured. Results: Side-to-side variability in the relative position of the patella to the femur was identified on anteroposterior imaging, with up to 14-degree difference between limbs noted. Overall, strong intraclass reliability and reproducibility of the measurements was achieved. Conclusions: The use of anteroposterior imaging alone does not reliably replace the lateral view for evaluation of femoral torsion. Circumstances of erroneous results when using the anteroposterior view were identified. Due to side-to-side differences, the anteroposterior technique cannot be recommended to determine anatomic torsion in femoral shaft fractures. The conventional technique using overlapping posterior condyles on the lateral view of the knee remains an important part of determining femoral torsion. Level of Evidence: Level IV.